Pemodelan Aplikasi Pemesanan E-Tiket pendakian Gunung Berbasis Android - Agus Suwarno; Edora Edora; Rifki Hamimi (Universitas Binaniaga Indonesia, 2023)
Ordering climbing tickets, which are getting more and more, requires a system to make it easier for climbers. Climbing activities are a hobby for climbers who like nature activities. Evidenced by the increasing number of enthusiasts of climbing activities today, booking climbing tickets is an important problem. Some climbers are willing to queue for 30 minutes and they even have to be willing to spend the night at the ticket reservation to get a climbing ticket. The solution to overcome this problem is to make an online ticket booking application. The method used in designing this application is the waterfall method. This design is made with an Android-based program so that it can be accessed anytime and anywhere. Purchasing tickets is easier because the ordering system is online. Hikers can easily see information about climbing so that it is more efficient.